The age of heretics a history of the radical thinkers who reinvented corporate management - Kleiner, Art. (San Francisco Jossey-Bass, 2008)
In this second edition of his bestselling book, author Art Kleiner explores the nature of effective leadership in times of change and defines its importance to the corporation of the future. He describes a heretic as a visionary who creates change in large-scale companies, balancing the contrary truths they can?t deny against their loyalty to their organizations. The Age of Heretics reveals how managers can get stuck in counterproductive ways of doing things and shows why it takes a heretical point of view to get past the deadlock and move forward.
"A Warren Bennis book"--P. [v].
Keywords: Organizational change -United States -Case studies